A Turkish translation and validation of the Sense of Agency Scale (SoAS-TR) - Çakmak, Işık Batuhan; Uygun, Şeyma; Kar, İrem; Göka, Erol (Frontiers in Psychology, 2026)
The sense of agency is defined as the experience of being the initiator of one’s actions and of influencing one’s surroundings. It represents a fundamental aspect of action monitoring, self-recognition, and the ability to distinguish one’s own actions from external events. Disturbances in the sense of agency have been reported across various psychiatric conditions, underscoring the need for valid self-report tools. However, no validated measure has been available to assess general agency beliefs in Turkish. This study aimed to adapt the Sense of Agency Scale into Turkish and evaluate its psychometric properties in an adult community sample. A total of 316 participants (65.5% women; mean age = 36.0, SD = 12.2) completed the survey, and 85 completed a 2-week retest. Confirmatory factor analyses supported the original two-factor structure—Sense of Positive Agency and Sense of Negative Agency—demonstrating good model fit, strong internal consistency, and moderate test–retest reliability. Construct validity was supported through associations with relevant constructs measured by the General Self-Efficacy Scale, the Rotter Internal–External Locus of Control Scale, the Multidimensional Assessment of Interoceptive Awareness, and the Free Will and Determinism Scale. Incremental validity analyses showed that the sense of negative agency explained significant additional variance in depressive symptoms, obsessive-compulsive traits, and schizotypal personality features beyond self-efficacy and locus of control, as assessed by the Beck Depression Inventory, the Obsessive-Compulsive Inventory–Revised, and the Schizotypal Personality Questionnaire, respectively. Associations with the Religiosity Scale were also examined to explore cultural dimensions of agency beliefs. Overall, the findings indicate that the Turkish adaptation is a reliable and valid instrument for assessing general agency beliefs across clinical and non-clinical contexts.